a vital past - Grigoryeva, Elena; Lidin, Konstantin (project baikal, 2021)
We lived and lived. But then, whoops!We found ourselves in other times…Timur Shaov. “Other times (listening to Galich once again)”Crises shaking our reality in the last decades happen so often that they overlap each other like roof tiles. Linear development of the second half of the twentieth century gave way to the era of cardinal changes. While building a new world, we strongly feel the need to preserve and comprehend the past. It is possible to understand the new only in comparison with the past. The disappearing world that consists of separate, isolated and selfcontained fragments is embodied in monuments of architecture. Images, techniques and practices of design and construction acquire a special meaning and new relevance in these new times. Wooden architecture of Siberia and stone merchant houses in Yalutorovsk, ancient churches and Leonidov’s avant-garde project, ruins of Stalin’s camps and the Korean Garden in Irkutsk are elements of the past that we need to understand the present. Protesting against the unification of tastes, breach of family relations and destruction of traditions, glocalization is on the rise.
Keywords: monuments of architecture; new times; glocalization